Synthesis and Characterization of High-Entropy Alloy Al𝑋FeCoNiCuCr by Laser Cladding - Xiaoyang Ye; Mingxing Ma; Wenjin Liu; Lin Li; Minlin Zhong; Yuanxun Liu; Qiwen Wu (Advances in Materials Science and Engineering)
High-entropy alloys have been recently found to have novel microstructures and unique properties. In this study, a novel Al𝑋FeCoNiCuCr high-entropy alloy was prepared by laser cladding. The microstructure, chemical composition, and constituent phases of the synthesized alloy were characterized by SEM, EDS, XRD, and TEM, respectively. High-temperature hardness was also evaluated. Experimental results demonstrate that the Al𝑋FeCoNiCuCr clad layer is composed of only BCC and FCC phases. The clad layers exhibit higher hardness at higher Al atomic content. The AlFeCoNiCuCr clad layer exhibits increased hardness at temperature between 400–700°C.